THE «NUMERICAL DATA ON LAND PROPERTY IN EUROPEAN RUSSIA» AS A SOURCE OF THE STUDY OF NOBLE LAND OWNERSHIP IN THE PROVINCES OF RIGHT BANK UKRAINE OF THE SECOND HALF OF THE XIX CENTURY - KRYSKOV, Andrii (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The purpose of the study is to introduce into scientific circulation and give a general description of a new statistical source for domestic researchers. Methodology of the research is based on the principles of historicism, systematization, scientificity, verification, authorial objectivity. General scientific methods (analysis, synthesis, generalization) are comprehensively applied. Special historical methods were also used, in particular statistical, historical-genetic and historical-systemic. The scientific novelty lies in the fact that for the first time a statistical source for research into the state of aristocratic land tenure in the 1890s was introduced into scientific circulation. Conclusions. In the Russian Empire, three land censuses were conducted to determine the state of land relations. The censuses of 1877 and 1905 were conducted according to a similar method, so their results are most often used by researchers. However, the time interval between these censuses is 28 years. Therefore, the document to which this article is devoted, is important for studying changes in aristocratic land tenure.